Percutaneous ultrasound-guided bowel biopsy of a pseudokidney mass - Maria Marsico; Tommaso Gabbani; Marocchi Margherita; Sarah Lunardi; Maria Rosa Biagini; Vito Annese (Turkish Journal of Gastroenterology, 2019)
-